Pemberdayaan Ibu-Ibu KWT dalam Pembuatan Kombucha: (Studi Kasus Sosialisasi di Desa Kuta Dalom) - Muhammad Rasyid Ridlo; Wawan Sukanda; Salwa Chania; Catur Adi Pangestu; Apin Choirunnisa Putri; Fida Abdurrofi6; Lusi Aprilia (Institut Teknologi dan Bisnis Semarang, 2024)
One of the healthy lifestyles that must be carried out by the community is to routinely consume probiotic drinks. This drink is an immuno booster drink that can increase the immune system or body resistance to fight all kinds of diseases caused by microorganisms. One type of probiotic drink is Kombucha, this drink is produced from the tea fermentation process. The Kombucha fermentation process uses microorganisms that come from the symbiosis of bacteria and fungi or known as Scoby. Kombucha tea is made by brewing sweet tea and adding Scoby to the tea solution. The purpose of this study was to empower women's farmer groups in making Kombucha. The method used is a case study applied in the real work lecture program of the University of Muhammadiyah Lampung which was held in Pekon Kutadalom, Gisting, Tanggamus on July 24-September 2023. The workshop was given to 30 women's farmer groups. The stages of activity in this method are observation and coordination with village officials, counseling/workshops, training in making Kombucha tea, and evaluation of activities. The results of observations and coordination with village officials were obtained to find out the existing problems. The community tends not to know what foods and drinks can increase the body's immunity. Continued with a workshop attended by 30 participants, participants were enthusiastic with various questions asked. The delivery of the material focused on the history of kombucha, benefits, and fermentation process, so that kombucha tea can be consumed regularly. The workshop on making probiotic kombucha tea drinks conducted for women farmer groups has been effective and can increase knowledge about the importance of routinely consuming probiotic drinks as body immunity.